Suicidality in first-generation, second-generation and non-immigrant youth in Canada - Ishika Obeegadoo; Mila Kingsbury; Kelly K. Anderson; Ian Colman (Journal of Migration and Health)
Background: The number of people migrating globally has drastically increased in the last two decades and continues to rise. Although adult migrants are typically in better health than the population they migrate to, the evidence regarding migrant children's health, and especially their mental health, is mixed. Objectives: To assess whether the prevalence of suicidal ideation and suicide attempt differs between first- and second-generation immigrant youth, compared to non-immigrants, and whether other sociodemographic factors moderate any associations. Methods: We analyzed a subsample of youth aged 15–17 years from the 2019 Canadian Health Survey on Children and Youth – a national, representative, cross-sectional survey. We conducted multivariable logistic regression analysis, with past-year suicidal ideation and suicide attempt as outcomes and migrant status as exposure. We also investigated whether sociodemographic factors (including sex, family income, parental divorce) moderated these associations using interaction terms. Results: Second-generation immigrants had almost twice the risk of first-generation immigrants and non-immigrants of having attempted suicide (OR 1.68, 95%CI: 1.07, 2.63). The association between second-generation immigrant status and suicide attempt was stronger among those not from low-income households (OR 2.04, 95%CI: 1.30, 3.21) and those with divorced parents (OR 5.19, 95%CI: 1.41, 19.12). The association between second-generation immigrant status and suicidal ideation was stronger among males (OR 1.78, 95% CI: 1.04, 3.07) and those with divorced parents (OR 4.13, 95%CI 1.40, 12.14). Additionally, some effects among first-generation immigrants varied by time since arrival. Relevance: The healthy immigrant effect with respect to suicidality does not appear to pass from the first-generation to the second-generation. The magnitude of effect among second generation immigrant youth varies according to other sociodemographic factors.